Adopting Capacity Planning in Agile Product Management for Operational Excellence - M, Deepika (Digital Repository of Theses, 2024)
In today's fast changing business world, organizations are significantly investing in development of streamlined products to gain competitive advantage. Behind these efforts lies the Product Lifecycle Management (PLM) team who is tasked to leveraging wide project management strategies to deliver innovative offerings synced with business requirements. One increasingly popular approach is Agile Product Management, focused on developing product strategies and creating roadmaps within an agile framework. This method emphasizes adaptability in planning and execution, enabling companies to quickly respond to feedback and create products that resonate deeply with customers. In integration to Agile Product Management, Agile capacity planning is a critical component of the planning process and a pivotal element of the strategizing phase. This practice involves assessing the productive engineering time at hand for an Agile team during a sprint or iteration. By understanding team capability, organizations can effectively allocate resources, manage workloads, and optimize productivity. his study aims to investigate the adoption of Agile capacity management planning within Product Management practices in organizations and its impact on operational performance. Scope creep often undermines capacity planning, leading to project inefficiencies and failures. To counteract this, capacity planning needs to be fine-tuned to handle changes effectively. By optimizing these practices, teams can better manage scope creep and enhance their operational excellence in agile product management.